Structural transition in Bcl-xL and its potential association with mitochondrial calcium ion transport - Rajan, Sreekanth (2015)
Bcl-2 family proteins are key regulators for cellular homeostasis in response to apoptotic stimuli. Bcl-xL, an antiapoptotic Bcl-2 family member, undergoes conformational transitions, which leads to two conformational states: the cytoplasmic and membrane-bound. Here we present the crystal and small-angle X-ray scattering (SAXS) structures of Bcl-xL treated with the mild detergent n-Octyl β-D-Maltoside (OM). The detergent-treated Bcl-xL forms a dimer through three-dimensional domain swapping (3DDS) by swapping helices α6-α8 between two monomers. Unlike Bax, a proapoptotic member of the Bcl-2 family, Bcl-xL is not converted to 3DDS homodimer upon binding BH3 peptides and ABT-737, a BH3 mimetic drug. We also designed Bcl-xL mutants which cannot dimerize and show that these mutants reduced mitochondrial calcium uptake in MEF cells. This illustrates the structural plasticity in Bcl-xL providing hints toward the probable molecular mechanism for Bcl-xL to play a regulatory role in mitochondrial calcium ion transport.